2021
DOI: 10.1021/acsapm.1c01058
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Cross-Linked Poly(β-Cyclodextrin) Particles as Promising Drug Delivery Materials

Abstract: One-pot synthesis of poly­(β-cyclodextrin) (p­(β-CD)) micro-/nanoparticles was accomplished using two different cross-linkers, divinyl sulfone (DVS) as p­(β-CD)-1 and trimethylolpropane glycidyl ether (TMPGDE) as p­(β-CD)-2. High gravimetric yields of 84 ± 4 and 62 ± 6%, respectively, were attained for p­(β-CD)-1 and p­(β-CD)-2 particles. The p­(β-CD)-1 and p­(β-CD)-2 particles had spherical shapes with 5.09 ± 0.24 and 0.60 ± 0.01 μm diameters, respectively, and exhibited good water dispersibility at physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…The surface morphology of prepared hydrogel was studied by SEM using an optical microscope (Vega 3, Tuscan). An optimum sized sample was placed on an aluminum stump coated with a thin layer of gold (~3000 Å) and photomicrographs were collected [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…The surface morphology of prepared hydrogel was studied by SEM using an optical microscope (Vega 3, Tuscan). An optimum sized sample was placed on an aluminum stump coated with a thin layer of gold (~3000 Å) and photomicrographs were collected [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, the absorbance ratio ( A 1079 / A 1023 ) of βCD-TPTE slightly decreased to 0.45. This decrease can be attributed to the peaks overlapping with the C–O–C stretching, which are associated with the formation of ether groups after cross-linking. , …”
Section: Resultsmentioning
confidence: 99%
“…Despite the widespread use of EP for βCD cross-linking, its toxicity and carcinogenicity have been documented, , rendering it unsuitable for water treatment applications. Consequently, alternative and more biocompatible cross-linkers have been reported in the literature for βCD cross-linking. Triphenylolmethane triglycidyl ether (TMTE) and trimethylolpropane triglycidyl ether (TPTE) have been selected in this study as alternative cross-linkers based on characteristics of lower toxicity, commercial availability, and similar epoxy groups suitable for cross-linking reactions, as present in EP. TMTE and TPTE have been reported as cross-linkers in biomaterials including dental materials and drug delivery materials. , Chung et al reported TMTE cross-linked photocurable material that aimed to be applied in dental applications showing low curing shrinkage, low water sorption, and low water solubility. Suner et al reported the biomaterials containing TPTE, which showed fast enzymatic degradation of 80–90% using pectinase and amyloglucosidase.…”
Section: Introductionmentioning
confidence: 99%
“…40 Even in one of the related studies reported by Demirci et al, the cross-linked CD particles of acyclovir were formed to provide a sustained release with respectable blood compatibility. 41 In our previous study, the polymer-free CD-IC nanofibers of acyclovir were successfully produced using highly water-soluble hydroxypropyl-β-cyclodextrin (HPβCD) for the purpose of fastdisintegrating oral delivery systems. 42 The potential of acyclovirincorporated polymeric nanofibers has also been reported for HSV-2 treatments 43 and ocular 44 and topical delivery 45 using PLGA, PCL, and polyvinylpyrrolidone (PVP) polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The administration dosage form of acyclovir includes tablets, cream, ointment, injection, and eye drops. , However, the therapeutic potential of acyclovir is diminished because of its limited water solubility, low bioavailability, and low membrane permeability. , On the other hand, there has been a notable effort to improve the therapeutic efficiency of this drug by improving its poor physicochemical properties using different approaches such as microemulsions, hydrogels, liposomes, nanoparticles, and CDs . Even in one of the related studies reported by Demirci et al, the cross-linked CD particles of acyclovir were formed to provide a sustained release with respectable blood compatibility …”
Section: Introductionmentioning
confidence: 99%